CoNi Alloy Nanoparticles Embedded in Metal–Organic Framework‐Derived Carbon for the Highly Efficient Separation of Xenon and Krypton via a Charge‐Transfer Effect. Issue 5 (1st December 2020) - Chen, Fuqiang; Ding, Jiaqi; Guo, Kaiqing; Yang, Liu; Zhang, Zhiguo; Yang, Qiwei; Yang, Yiwen; Bao, Zongbi; He, Yi; Ren, Qilong
Abstract: Separation of Xe and Kr is one of the greatest challenges in the gas industries owing to their close molecular structure and similar properties. Energy‐effective adsorption‐based separation using chemically stable carbon adsorbents is a promising technology. We propose a strategy for Xe/Kr separation using MOF‐derived metallic carbon adsorbents. M‐Gallate (M=Ni, Co) were used as precursors to fabricate CoNi alloy nanoparticles embedded carbon adsorbents by one‐step auto‐reduction pyrolysis. The optimal NiCo@C‐700 exhibits record‐high IAST selectivity (24.1) and Henry's selectivity (20.1) of Xe/Kr among reported carbon adsorbents. DFT calculations, local density of states calculation, charge density difference, and Bader charge analysis reveal the great affinity with Xe benefits from the presence of Ni or CoNi nanoparticles as a result of more charge transfer from Xe than Kr to metal, thus providing higher binding energy. Breakthrough experiments further verify NiCo@C‐700 a promising candidate for Xe/Kr separation. Abstract : Highly efficient separation of Xe/Kr is achieved on CoNi alloy nanoparticles embedded MOF‐derived carbon adsorbents via charge‐transfer effect. It affords record‐high IAST selectivity and Henty's selectivity of Xe/Kr mixture.